1995
DOI: 10.1364/ao.34.001003
|View full text |Cite
|
Sign up to set email alerts
|

Mode coupling in large-diameter polymer-clad silica fibers

Abstract: Intermodal diffusion in a large-diameter plastic-clad silica step-index fiber is measured with a near-field projection of the modal pattern onto a CCD camera. The diffusion process is found to obey a 1/θ(2) dependence (where θ is the axis-crossing angle of the mode). The diffusion constant is estimated to be 1.3 × 10(-5) rad(2) m-(1). The contribution of mode mixing to evanescent-wave spectroscopy in such fibers is discussed. When all bound meridional modes are launched, the effect of diffusion is a small redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Analysis of data on mode coupling from a variety of step-index multimode optical fibers (Table ) reveals that mode coupling is a strong function of fiber attenuation. ,,, This attenuation- dependent mode coupling leads to the rapid development of a steady-state distribution of modes. Another source of mode coupling arises from inhomogeneities in the refractive index of the fiber cladding at the core/cladding interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of data on mode coupling from a variety of step-index multimode optical fibers (Table ) reveals that mode coupling is a strong function of fiber attenuation. ,,, This attenuation- dependent mode coupling leads to the rapid development of a steady-state distribution of modes. Another source of mode coupling arises from inhomogeneities in the refractive index of the fiber cladding at the core/cladding interface.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the MPD in the sensing zone is essential for quantitative evanescent-wave detection and for effective design of a wide range of sensors, including those based on refractive index, absorbance, or fluorescence detection. Mode coupling, which is due primarily to scattering and absorption within the fiber core and at the core−cladding interface, results in a loss of some higher-order core modes into the cladding and a concentration of lower-order (on-axis) modes that increases with distance from the source . As a result, mode coupling in a multimode evanescent-wave sensor alters the sensitivity of the sensor and increases the analyte-independent optical loss.…”
mentioning
confidence: 99%
“…Thus, for a given L, η j directly defines the sensitivity [13]. Owing to the high-order modes being excited repeatedly at the first transition of each segmented region, the SS EW sensor can effectively stimulate the fiber low-order modes to the high-order modes [21]. When ξ (the number of segments) increases, the stimulation from the loworder modes to the high-order modes will be more effective.…”
Section: Theorymentioning
confidence: 99%
“…The absorbable power ratio is derived by ¼ p a / p t , and p t is the total pump power. Some experiments have demonstrated that the mode coupling coefficient is not a constant, but is proportional to 1/z 1/2 [7], so in the following calculation we chose ¼ 0 /z 1/2 instead of a constant . The total absorption efficiency versus the fiber length by both calculation and fitting is given in Figure 5.…”
Section: Theorymentioning
confidence: 99%